2017
DOI: 10.1186/s12884-017-1311-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rapid immunoassays for rupture of fetal membranes

Abstract: BackgroundRupture of membranes (ROM) before the onset of uterine contractions, particularly in pregnancies less than 37 weeks gestational age, is a common diagnostic problem in obstetrical practice. Timely detection of ROM is vital to support gestational age-specific interventions to optimize perinatal outcomes and minimize the risk of serious complications such as preterm delivery, fetal distress and maternal/fetal infections. Rapid bedside immunoassay tests designed to detect amniotic fluid proteins in cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Varied etiopathogenesis of preterm delivery resulted from the fact that in the past decade identification of numerous cytokines and molecules connected with preterm delivery has not brought any significant progress in the differential diagnosis of early preterm delivery and false preterm delivery. The majority of the commercially available tests is based on the estimation of insulin-like growth factor binding protein (IGFBP-1) in combination with other molecules, for example, alpha-fetoprotein (AFP) or interleukin 6 (IL-6) [ 15 18 ]. Additionally, a majority of these immunoassays are used for detection and confirmation of fetal membrane rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Varied etiopathogenesis of preterm delivery resulted from the fact that in the past decade identification of numerous cytokines and molecules connected with preterm delivery has not brought any significant progress in the differential diagnosis of early preterm delivery and false preterm delivery. The majority of the commercially available tests is based on the estimation of insulin-like growth factor binding protein (IGFBP-1) in combination with other molecules, for example, alpha-fetoprotein (AFP) or interleukin 6 (IL-6) [ 15 18 ]. Additionally, a majority of these immunoassays are used for detection and confirmation of fetal membrane rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque es considerado por muchos investigadores como el estándar de oro para el diagnóstico de RPM, (11,13,14) la prueba de la amniocentesis es un procedimiento invasivo con riesgos inherentes que incluyen sangrado (desprendimiento de la placenta), infección, rotura de membranas de forma iatrogénica, y el aborto involuntario. Por estas razones, se necesita urgentemente una prueba rápida, precisa, barata y no invasiva para el diagnóstico de la RPM (15).…”
Section: Discussionunclassified
“…Another test, called ROM Plus® (Clinical Innovations, Salt Lake City, UT USA), is designed to detect both placental protein 12 and alpha-fetoprotein as indicators of amniotic fluid. Compared to Amnisure, a prospective study on 111 women showed comparability in diagnostic accuracy [19].…”
Section: Confirmation Of Diagnosis and Work-upmentioning
confidence: 99%